Open Innovation, Technology Platform, Competitive Advantage UMKM Di Sulawesi Selatan - Suharto Suharto; Rachmawaty Rachmawaty; Andi Aris Mattunruang* (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to examine the effect of open innovation on the competitive advantage of SMEs and to examine the role of technology platforms in moderating the effect of open innovation on the competitive advantage of SMEs. The variables examined in this study are open innovation as the independent variable, competitive advantage of SMEs as the dependent variable. The technology platform is tested as a variable that moderates the effect of open innovation on the competitive advantage of MSMEs. The sample in this study was 75 MSMEs in South Sulawesi, Indonesia using indirect (online) and direct (offline) questionnaire surveys. Hypothesis testing is done by simple regression analysis and Moderate Regression Analysis (MRA). The results of the study show that the two hypotheses proposed are supported, namely open innovation has a positive effect on the competitive advantage of MSMEs and the technology platform strengthens the relationship between open innovation and the competitive advantage of MSMEs.